Pathophysiology and Pre-Operative Evaluation of Patients at Risk for Intraoperative Floppy Iris Syndrome (IFIS) - Cantrell, Matthew A.; Bream-Rouwenhorst, Heather R.; Watts, Christopher; Oetting, Thomas A. (IntechOpen, 2013)
None